Anonymous

# Solve for x?

How to solve (4/x+1)-(2/x-1)=(3x+6/x^2-1)

### 2 Answers

Relevance

- EarthlingLv 46 years agoFavorite Answer
( 4 / ( x+1 ) ) - ( 2 / ( x-1 ) ) = ( ( 3x+6 ) / ( x^2-1 ) )

finding LCM for LHS, (multiplying denominators and cross multiplying numerators and denominators)

(4x - 4 - 2x - 2) / (x^2 - 1) = ( ( 3x+6 ) / ( x^2-1 ) ) --------- ( (a+b) (a-b) ) = (a^2 - b^2)

cancelling the denominators,

2x - 6 = 3x + 6

x = -12

- Anonymous6 years ago
you should try first

Still have questions? Get your answers by asking now.